Andragogy-based learning model for intergenerational salted egg businesses in Tangerang Regency - Mustofa Kamil; Sri Yanti; Dadang Yunus; P. Purnomo (Inovasi Kurikulum, 2024)
This study examines the andragogical learning model in the context of intergenerational businesses, specifically within the salted egg artisans community in Tangerang Regency. Intergenerational businesses face significant challenges in transferring knowledge and values between generations, often experiencing shifts due to differences in perspectives and priorities. The andragogical approach emphasizes the importance of learning relevant to adults' needs and life experiences. This approach involves collaboration between older and younger generations in family businesses to address shared challenges. This research employs a case study method to identify effective learning models for managing knowledge transfer and values within the salted egg artisans community. The results indicate that an andragogy-based collaborative learning model, which involves both generations in the learning process through practical experience and joint discussions, effectively enhances business sustainability. This approach not only improves technical skills and knowledge but also strengthens the understanding of traditional values and modern innovations, which are crucial for the sustainability and success of intergenerational businesses. The study suggests the need for flexibility and adaptability in learning models to ensure the successful transfer of knowledge and values between generations in family businesses. AbstrakPenelitian ini mengkaji model pembelajaran berbasis andragogi dalam bisnis intergenerasi, khususnya pada komunitas pengrajin telur asin di Kabupaten Tangerang. Bisnis intergenerasi menghadapi tantangan besar dalam transfer pengetahuan dan nilai antar generasi, yang sering kali mengalami pergeseran seiring dengan perbedaan cara pandang dan prioritas. Pendekatan andragogi menekankan pembelajaran yang relevan dengan kebutuhan dan pengalaman hidup orang dewasa, dan dalam bisnis keluarga, pendekatan ini melibatkan kolaborasi antara generasi tua dan muda untuk mengatasi tantangan bersama. Penelitian ini menggunakan metode studi kasus untuk mengidentifikasi model pembelajaran yang efektif dalam mengelola transfer pengetahuan dan nilai dalam komunitas pengrajin telur asin. Hasil penelitian menunjukkan bahwa model pembelajaran collaborative learning berbasis andragogi, yang melibatkan kedua generasi dalam proses belajar melalui praktik nyata dan diskusi bersama, efektif dalam memperkuat keberlanjutan usaha. Model collaborative learning meningkatkan keterampilan teknis dan pengetahuan, juga memperkuat pemahaman tentang nilai-nilai tradisional dan inovasi modern, yang keduanya penting untuk keberlanjutan dan kesuksesan bisnis intergenerasi. Penelitian ini menyarankan perlunya fleksibilitas dan adaptabilitas dalam model pembelajaran untuk memastikan keberhasilan transfer pengetahuan dan nilai antar generasi dalam bisnis keluarga.Kata Kunci: andragogi; bisnis intergenerasi; pembelajaran kolaboratif; transfer nilai; transfer pengetahuan